The framework for resilient industry : a holistic approach for developing economies - Kumar, Narinder; Sood, Kiran; Özen, Ercan; Grima, Simon (Emerald studies in finance, insurance, and risk management, 2024)
Countries such as India, Pakistan, Bangladesh, and Sri Lanka have economies that are categorised as capital deficit, whereas economies with abundant capital - such as those in Western Europe and North America - have lost little value in comparison during the global pandemic and other economic periods of this downturn. It is therefore a question of resilience that separates these developing economies. The Framework for Resilient Industry examines the historical background of the Indian industry, its current status, and future opportunities and challenges. The chapters frame the historical context of the Indian industry and delves into region-specific issues such as micro, small, and medium enterprises (MSMEs), economic policy, risk management and sustainable industries. The findings are valuable to policymakers, industrialists, and governments, both state and central, through efficient analysis. Academics, researchers, and students will also benefit from this discourse on economic resiliency. Emerald Studies in Finance, Insurance, and Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.